Klasifikasi Tingkat Risiko K3 pada Proyek Konstruksi Berkelanjutan Berbasis Matriks Risiko AS/NZS 4360 - Dimas Prasetyo; Imam Mustofa (Jurnal Konstruksi, 2026)
High-rise building construction projects involve a high level of hazards and uncertainty, requiring the systematic implementation of occupational safety risk management. This study aims to identify and classify occupational health and safety (OHS/K3) risk levels and to formulate control measures for high-rise building construction projects. The research method employs a quantitative approach through the distribution of questionnaires to 39 respondents, with risk analysis based on the standard AS/NZS 4360:2004 risk matrix. The results indicate that 8% of the variables fall into the high-risk category, 40% into the medium-risk category, and 52% into the low-risk category. High risks are primarily associated with structural work activities and field operations that have the potential to cause serious accidents. The contribution of this study lies in the presentation of measurable and applicable OHS risk mapping, along with risk-level-based control recommendations, which can serve as a practical reference for project managers in improving the effectiveness of OHS management system implementation in sustainable building construction projects.